Dane
a = 3
b=9
Równanie
(2x – a)(x+2) = (2x – a)(2x - b)
ma dwa rozwiązania. Są to liczby:


Odpowiedź :

Odpowiedź:

(2x - a) (x + 2) = (2x - a) (2x - b)

(2x - 3) (x + 2) = (2x - 3) (2x - 9)

2x² + 4x - 3x - 6 = 4x² - 18x - 6x + 27

2x² + x - 6 = 4x² - 24x + 27

2x² - 4x² + x + 24x - 6 - 27 = 0

- 2x² + 25x - 33 = 0

a = - 2,  b = 25,  c = - 33

Δ = b² - 4ac =  25² - 4 * (- 2) * (- 33) = 625 - 264 = 361

√Δ = 19

x₁ = (-b -√Δ) / 2a = (- 25 - 19)/2 * (-2) = - 44/ - 4 = 11

x₂ = (- b + √Δ) /2a = (- 25 + 19) / 2 * (-2) = - 6/ -4 = 1,5

x₁ = 11

x₂ = 1,5

Szczegółowe wyjaśnienie: